Blister - Shreve, Susan Richards (New York, NY : Scholastic Inc., 2002)
When a family tragedy occurs, ten-year-old Alyssa "Blister" Reed changes schools, moves to an apartment with her depressed mother while her father gets his own place, and tries to believe her grandmother, who tells her she is "elastic" and can handle it all.
G6
Keywords: Family problems -- Fiction; Moving, Household -- Fiction; Schools -- Fiction; Cheerleading -- Fiction